2013
DOI: 10.1007/s00595-013-0813-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmasked renal impairment and prolonged hyperkalemia after unilateral adrenalectomy for primary aldosteronism coexisting with primary hyperparathyroidism: report of a case

Abstract: We herein report the case of a patient with critical hyperkalemia after unilateral adrenalectomy (ADX) for aldosterone-producing adenomas, which were coexisting with primary hyperparathyroidism. A right adrenal tumor oversecreting mineral corticoid was identified in a 62-year-old female whose kidney function had been impaired due to primary hyperaldosteronism and hyperparathyroidism. The ADX improved her hypertension with normalization of the plasma aldosterone concentration, but without adequately increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the context of unilateral adrenalectomy for PA, the discovery of normal to high plasma potassium (4.5 mmol/L) or labile BP could indicate a temporarily insufficient adaptation of the remaining adrenal gland. Such a situation has been reported in previous studies and has been attributed to a transient or prolonged hypoaldosteronism associated with a discrepancy between plasma renin levels and a lack of information concerning volemic status (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the context of unilateral adrenalectomy for PA, the discovery of normal to high plasma potassium (4.5 mmol/L) or labile BP could indicate a temporarily insufficient adaptation of the remaining adrenal gland. Such a situation has been reported in previous studies and has been attributed to a transient or prolonged hypoaldosteronism associated with a discrepancy between plasma renin levels and a lack of information concerning volemic status (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 69%
“…The current treatment consists of removing the adrenal gland responsible for aldosterone hypersecretion (2). Numerous studies have reported post-unilateral adrenalectomy complications, which can consist of severe hyperkalemia related to adrenal insufficiency (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperkalemia is an important complication of adrenalectomy for PA. It is generally rare and transient and presents shortly after surgery [3][4][5][6][7][8]. Hyperkalemia is thought to be caused by hypoaldosteronism resulting from the removal of APA.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenalectomy in patients of unilateral APA is expected to be biochemically and clinically curative and to reduce cardiovascular complications [2]. In contrast, some patients with APA develop hyperkalemia after adrenalectomy [3][4][5][6][7][8]. Although postoperative hyperkalemia may have been caused by the insufficiency of aldosterone secretion from the zona glomerulosa of the adrenal cortex, few studies had examined plasma aldosterone concentration (PAC) in patients with postoperative hyperkalemia in detail [8,9].…”
mentioning
confidence: 99%